Governance and effects of public R&D subsidies: evidence from China - Guo, Di; Guo, Yan; Jiang, Kun (Elservier, 2018)
This study examines the effects of public research and development (R&D) subsidies and the governance of such subsidies on firm productivity based on the analysis of a firm-level panel dataset between 1998 and 2007 in China. It is found that public R&D subsidies tend to support more productive firms and the productivity of these government-backed firms is improved further after they get the government support. Less attention is paid to the observable or measurable performance measurements in ex-ante project selection, and the ex-post effects are stronger when the governance of the public R&D subsidies becomes more decentralized due to an exogenous policy change. In other words, better decentralization of governance is associated with more pronounced effects of R&D subsidies. Identification concerns are addressed with various approaches to confirm the treatment effect of public R&D subsidies and the governance of such subsidies.